Biosurveillance of vibrio parahaemolyticus in raw salad vegetables at pre-harvest, retail and domestic kitchen levels - Robin, Tunung (2012)
Vibrio parahaemolyticus is known to be one of the leading causes of human gastroenteritis associated with seafood consumption. However recent foodborne outbreaks throughout the world have been intensively linked to consumption of fresh fruits, vegetables and unpasteurized juices, and cross-contamination of raw fruits and vegetables with seafood represents a potential mode of transmission of V. parahaemolyticus to humans. The purpose of this study was to carry out a biosurvellance of V. parahaemolyticus in raw salad vegetables at pre-harvest, retail and domestic kitchen level in Malaysia. A combination of Most Probable Number -Polymerase Chain Reaction (MPN-PCR) method was applied to detect the presence of total V.parahaemolyticus pathogenic V. parahaemolyticus harboring tdh and trh genes, and to enumerate their density in the samples. The characteristics of V.parahaemolyticus profiles of the strains isolated from vegetables were also assessed by antibiotic resistance and RAPD-PCR. A domestic kitchen simulation study was conducted to provide decontamination data and information for the estimation of the risk of acquiring vibriosis from consumption of raw vegetables using Quantitative Risk Assessment (QRA) deterministic approach. From the study, it was revealed that the presence of V. parahaemolyticus could be detected in the samples. At pre-harvest level, a total of 146 samples of raw vegetables, soil, water, animal manure and surface swab samples collected from three vegetable farms and three packing houses at Cameron Highlands, Pahang were analyzed. The occurrence of total V. parahaemolyticus (toxR) detected was relatively low (13.70%), while the presence of V. parahaemolyticus harboring tdh and trh virulent genes were 1.37% and 0%, respectively. The maximum concentration of total V. parahaemolyticus in the samples was 1100 MPN/g, while V. parahaemolyticus tdh+ was 7.3 MPN/g and V. parahaemolyticus trh+ was <3MPN/g. Meanwhile, at retail level, 276 samples of vegetables commonly eaten raw in Malaysia were purchased from two supermarkets and two wet markets located in Selangor, Malaysia and were analyzed. The occurrence of total V. parahaemolyticus detected in the vegetables was 20.65%, with concentration range of <3 MPN/g to >2400 MPN/g. Pathogenic V. parahaemolyticus tdh+ was detected at the rate of 11.96%, while for V. parahaemolyticus trh+, the prevalence was 10.14%. The maximum density of V. parahaemolyticus tdh+ and trh+ in the samples were 39 MPN/g and 15 MPN/g, respectively. The numbers of total and pathogenic V. parahaemolyticus present in the samples from pre-harvest and retail level were found to be lower (maximum of 103) than the infectious dose (106) that could cause illness in healthy individuals. At domestic kitchen level, simulation of the handling of raw vegetables in domestic kitchens by washing was designed to imitate real events in domestic kitchens as much as possible to give a realistic quantitative data on how V. parahaemolyticus could be reduced by washing procedures. Five washing steps were applied in this simulation, and both naturally and artificially contaminated vegetables were used. The total prevalence of V. parahaemolyticus in the naturally contaminated samples was 75.00%, with mean concentration 108.95 MPN/g. It was found that washing by rinsing the vegetables vigorously in collected tap water could reduce the numbers up to 0.58 log reduction compared to washing using other methods, which were lower but still significantly reduced V. parahaemolyticus in the vegetables. A total of 46 V. parahaemolyticus isolates were recovered by plating method and confirmed by PCR. None of the isolates were detected to carry virulence genes tdh and trh. Antibiotic resistance profiling indicated that multi-resistance V.parahaemolyticus might be wide-spread in the study area. The isolates showed multi-resistance to as many as 14 antibiotics tested, with 93.48% resistance to Nalidixic Acid and mostly susceptible to Impinem (4.35% resistance). High Multiple Antibiotic Resistance (MAR) indices were detected in this study, with more than 19.57% of the isolates had a MAR index value of 0.5, indicating that the isolates might originate from sources that were exposed to antibiotics. Clustering of V. parahaemolyticus isolates based on RAPD-PCR profiles suggested that most of the strains from the same sampling locations were clustered into the same group,although some strains from different sampling locations were found clustered in the same group. A preliminary step-wise risk assessment was carried out to estimate the risk (probability of infection leading to illness) posed by V. parahaemolyticus from the consumption of raw vegetables in Malaysia, and the estimation was focused on the different races in Malaysia due to the differences in the consumption pattern of raw vegetables among the races. An exponential dose-response model was used. The estimated annual number of cases of vibriosis acquired from the consumption of raw vegetables was 20,930 cases per 100,000 Malaysian populations. The risk was higher for Malays (31,496 cases per 100,000 population), followed by Chinese (9,137 cases per 100,000 population), and Indians (2,568 cases per 100,000 population). After washing vegetables by rinsing in tap water (highest log reduction), the risk of illness was reduced from 20,930 cases per 100,000 Malaysian populations to 20,853 cases per 100,000 populations. The results suggest that raw vegetables act as a transmission route for V.parahaemolyticus and thus pose a risk for consumers. It is recommended to carry out a future cross-contamination study to determine the source or point of contamination along the distribution line of vegetable produce. Further studies on a bigger scale are also recommended for a better understanding on the presence of V.parahaemolyticus in raw vegetables and the risks involved when consuming raw vegetables.